2017
DOI: 10.1038/s41467-017-01878-6
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Crtc2 controls whole body energy metabolism via a miR-34a-Fgf21 axis

Abstract: Liver plays a crucial role in controlling energy homeostasis in mammals, although the exact mechanism by which it influences other peripheral tissues has yet to be addressed. Here we show that Creb regulates transcriptional co-activator (Crtc) 2 is a major regulator of whole-body energy metabolism. Crtc2 liver-specific knockout lowers blood glucose levels with improved glucose and insulin tolerance. Liver-specific knockout mice display increased energy expenditure with smaller lipid droplets in adipose depots.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 40 publications
4
45
0
Order By: Relevance
“…Acute or chronic, overactivated or deactivated CRTC2 may have various effects on hepatic insulin signaling . We agreed with the conclusion from Han et al that tight regulation of hepatic CRTC2 function is critical in the maintenance of energy and metabolic homeostasis in mammals. Proper restoration of TAC‐suppressed CRTC2 activation is of help to prevent and alleviate TAC‐induced metabolic disorders.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Acute or chronic, overactivated or deactivated CRTC2 may have various effects on hepatic insulin signaling . We agreed with the conclusion from Han et al that tight regulation of hepatic CRTC2 function is critical in the maintenance of energy and metabolic homeostasis in mammals. Proper restoration of TAC‐suppressed CRTC2 activation is of help to prevent and alleviate TAC‐induced metabolic disorders.…”
Section: Discussionsupporting
confidence: 91%
“…Canettieri et al found that rat hepatocytes with adenoviral overexpression of CRTC2 were more responsive to acute insulin stimulation, whereas mice with adenovirus CRTC2 RNAi showed almost undetectable IRS2 expression and reduced AKT phosphorylation in the liver. In contrast, other studies showed that either whole‐body or liver‐specific CRTC2 knockout mice presented markedly better glucose and insulin tolerance under high‐fat diet conditions but not in the chow‐fed state . Taken together, it seems that the role of CRTC2 in hepatic insulin sensitivity is dependent on certain circumstances (eg, diet and fatty liver).…”
Section: Discussionmentioning
confidence: 86%
“…Unlike in the previous studies, CRTC2-KO mice lacking the entire CRTC2 protein displayed reduced blood glucose levels and improved glucose tolerance compared with their wild-type littermates, which is consistent with the results of earlier acute knockdown studies. Indeed, we were able to confirm the results of the latter study by using liver-specific CRTC2-KO mice, and showing that CRTC2 is a crucial regulator of glucose metabolism by controlling hepatic gluconeogenesis in vivo [25].…”
Section: Glucose Metabolismsupporting
confidence: 76%
“…We have explored the role of CRTC2 in hepatic lipid metabolism by using liver-specific CRTC2-KO mice [25]. Unlike previous reports that used whole-body CRTC2-KO mice, we found that liver-specific depletion of CRTC2 ameliorates lipid accumulation in the liver under conditions of diet-induced obesity (DIO).…”
Section: Lipid Metabolismmentioning
confidence: 77%
“…Substrate switching and efficient nutrient utilization in the liver are key for maintaining metabolic homeostasis at the organismal level (Han et al, 2017;Rui, 2014). Specifically, SIRT1-PGC1a regulate glucose and fat metabolism in hepatocytes.…”
Section: Fed Micrornas Regulate Hepatic Fao and Organismal Energy Hommentioning
confidence: 99%